211. CyberKnife SBRT: Monte Carlo (MC) vs. Ray Tracing (RT) in retrorbital and subcutaneous tumors. (December 2018) - Micali, A.; Midili, F.; Brogna, A.; Pasquale, A. Di; Mongelli, V.; Siragusa, C.; Angiocchi, M.C.; Inferrera, P.; Lanzafame, S.; Ielo, I.
Abstract : Purpose: Monte Carlo (MC) is indicated as the "gold standard" of dose calculation algorithms. MC predicts the absorbed dose by simulating electron and photon transport and takes into account the electronic disequilibrium due to tissues heterogeneity. In this study, MC algorithm was used first to re-calculate and then to re-optimize RT plans of retrorbital and subcutaneous tumors in order to investigate differences in the dose distribution and PTVcoverage. Methods: Firstly, 10 retrorbital and 10 subcutaneous RT and MC re-calculated plans were generated with the aim of evaluate the PTVcoverage. Then, in the "Sequential" workspace, the RT plans were optimized using the MC algorithm, setting medium resolution and 1% statistical uncertainty, leaving the other optimization parameters (collimators size, max Monitor Units (MU) per beam and per node, constraints and objectives) unchanged. In the "Evaluate" workspace, MC plans were calculated in high resolution and were prescribed at the same isodose of the RT ones and compared. The same process was repeated setting 0.5% statistical uncertainty. Results: For the retrorbital tumors, the comparison between RT and only re-calculated MC plans did not show significant differences in the PTVcoverage and in the dose distributions. Instead, MC optimized plans with 1% statistical uncertainty always showed a PTVcoverage lower than RT one (Fig. 1): V100 RT [95.4–99.08]% vs. V100 MC [78.7–80.1]%. When MC plans were optimized with 0.5% statistical uncertainty, the PTVcoverage was similar to the RT one (Fig. 2). Furthermore, RT and MC plans had comparable beams number and total MU. For the subcutaneous tumors, in all the comparison performed, no significant differences were registered. Conclusion: For retrorbital and subcutaneous tumors, the negligible difference between the optimized MC plans with 0.5% statistical uncertainty and the RT ones, justified the use of the RT algorithm, involving a corrected prescription isodose choice and a right DVH evaluation.